Science + Triathlon 2015 World Conference (INSEP, 2015)
Abstractband der Internationalen Konferenz Wissenschaft + Triathlon 2015 (Science + Triathlon 2015 World Conference). Inhalt: Darren Smith (AUS) - The mysterious case of strength within triathlon Inigo Mujika (ESP) - Scientific bases of strength training for endurance performance Keith Baar (USA) - Nutrition to optimize strength training adaptations Dr. Margo Mountjoy (CAN) - Relative Energy Deficiency in Sport Sergio Migliorini (ITA) - Stress fracture of the lower limbs in athletes Sergio Santos (POR) - Training Load in Olympic Triathlon: Trying to understand individual needs Jamie Stanley (AUS) - Training Monitoring in Elite Triathletes Yann Le Meur (FRA) - Functional overreaching: the key to peak performance during the taper? Romuald Lepers (FRA) - Mental fatigue and performance in triathlon Joel Fillol (CAN) - Consistency over three Olympic Games: A case study on Simon Withlfield Benjamin Maze and Frank Bignet (FRA) - Accompany singularity in a federal project of performance - Case of the French Triathlon Federation Kevin Curell (GBR) - Unleash the Power of food to improve triathlon performance The route of Yannick Bourseaux (FRA) Paratriathlon classification system Iñigo Mujika (ESP) - Physiology and training of a World Champion paratriathlete Yannick Guézennec (FRA) - Motivation and methods for altitude training in triathletes Mike Tipton (GBR) - Lower water temperature research FINA/IOC/ITU Christophe Hausswirth (FRA) - Does heat training camp influence performance in temperate environment? Paul Laursen (NZL) - Keeping your cool in extreme conditions: strategies to maximise performance